2000
DOI: 10.1084/jem.192.6.881
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 8 Receptor Deficiency Confers Susceptibility to Acute Experimental Pyelonephritis and May Have a Human Counterpart

Abstract: Neutrophils migrate to infected mucosal sites that they protect against invading pathogens. Their interaction with the epithelial barrier is controlled by CXC chemokines and by their receptors. This study examined the change in susceptibility to urinary tract infection (UTI) after deletion of the murine interleukin 8 receptor homologue (mIL-8Rh). Experimental UTIs in control mice stimulated an epithelial chemokine response and increased chemokine receptor expression. Neutrophils migrated through the tissues to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
209
2
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(220 citation statements)
references
References 23 publications
6
209
2
3
Order By: Relevance
“…Disease severity is controlled by the murine IL-8R homologue (mIL-8Rh) and mIL-8Rh -/-mice develop acute pyelonephritis, bacteremia and renal scarring due to neutrophil entrapment in the tissues [15,40]. Genetic defects in the IL-8R have also been detected in patients prone to acute pyelonephritis [41]. The present study emphasized the potential for host control of unresponsiveness to UTI, as abrogated TLR4 signalling protected against inflammation and symptoms.…”
Section: Discussionmentioning
confidence: 68%
“…Disease severity is controlled by the murine IL-8R homologue (mIL-8Rh) and mIL-8Rh -/-mice develop acute pyelonephritis, bacteremia and renal scarring due to neutrophil entrapment in the tissues [15,40]. Genetic defects in the IL-8R have also been detected in patients prone to acute pyelonephritis [41]. The present study emphasized the potential for host control of unresponsiveness to UTI, as abrogated TLR4 signalling protected against inflammation and symptoms.…”
Section: Discussionmentioning
confidence: 68%
“…In this context, it was observed that the use of peptide and non-peptide CXCR2 antagonists, truncated GROa(8-73) and SB 455821, respectively, blocked the in vitro and in vivo MIP-2-induced neutrophil migration [10,29]. In addition, it was demonstrated that the genetic disruption of CXCR2 blocked the neutrophil recruitment observed in inflammatory disease models of polynephritis and Lyme arthritis, resulting in resistance to pathology [30][31][32]. Repertaxin is a novel noncompetitive allosteric inhibitor of CXCR1 and CXCR2, and is an active blocker of neutrophil chemotaxis in humans and rodents [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…However, the two UPEC strains induced markedly different stimulation profiles of proinflammatory mediators in the kidneys of Lps n and Lps d mice, suggesting that different bacterial factors produced by the UPECs may be implicated in the activation of distinct TLR4-dependent and -independent signaling pathways. MIP-2 and its human counterpart IL-8 play key roles in the migration of neutrophils to infected mucosal sites to protect them against invading pathogens (41,42,57). The two UPECs stimulated MIP-2 mRNA expression and protein secretion in both Lps n kidney and cultured Lps n MCDs through a main TLR4-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%